The relationship between geographical mobility and education-job mismatches - Maud Hensen; Robert de Vries (European Regional Science Association (ERSA), 2004)
In this paper we investigate the relationship between geographical mobility and education-job mismatches. School-leavers might adjust to local labour market frictions by accepting some education-job mismatch combined with a mobility decision. We focus on the relationship between the mobility decision and the following education-job mismatches: a job below the educational level, outside the educational field, part-time or flexible jobs at the beginning of the career. For this purpose we use data about school-leavers from secondary education and higher vocational education in the period 1996-2001. The analysis is conducted at a disaggregated spatial level to incorporate differences in behaviour of school-leavers at the regional level. We find that school-leavers who are more mobile have a lower probability to have a job below the acquired educational level compared with school-leavers who are less mobile. Moreover, school-leavers who are more mobile experience especially a lower probability of a part-time or a flexible job. This result suggests that school-leavers not only try to prevent a job below the acquired educational level, but also other education-job mismatches in their mobility decision.
Keywords: 330